1999
DOI: 10.1161/01.atv.19.12.2945
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia of ApoE2(Arg 158 -Cys) and ApoE3-Leiden Transgenic Mice Is Modulated Predominantly by LDL Receptor Expression

Abstract: Abstract-To investigate the relative roles of the LDL receptor-and non-LDL receptor-mediated pathways in the clearance of apolipoprotein E (apoE) variants in vivo, we have generated apoE2(Arg 158 -Cys) (apoE2) and apoE3-Leiden transgenic mice deficient for the endogenous mouse Apoe and Ldl receptor genes (ApoeϪ/Ϫ.LdlrϪ/Ϫ mice). Unexpectedly, on the ApoeϪ/Ϫ.LdlrϪ/Ϫ background, expression of neither apoE2 nor apoE3-Leiden results in a decrease of the hyperlipidemia. In contrast, serum cholesterol levels are incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…As previously reported (30), for mice on a normal diet, fasting plasma triglyceride and cholesterol levels were significantly higher in A mApoe Ϫ/Ϫ /htgApoe3L mice than in mApoe Ϫ/Ϫ /htgApoe3 mice and levels in mApoe Ϫ/Ϫ / htgApoe2 mice were significantly elevated as compared with either mApoe Ϫ/Ϫ /htgApoe3 or mApoe Ϫ/Ϫ /htgApoe3L mice (Fig. 1A).…”
Section: Downloaded Fromsupporting
confidence: 86%
See 1 more Smart Citation
“…As previously reported (30), for mice on a normal diet, fasting plasma triglyceride and cholesterol levels were significantly higher in A mApoe Ϫ/Ϫ /htgApoe3L mice than in mApoe Ϫ/Ϫ /htgApoe3 mice and levels in mApoe Ϫ/Ϫ / htgApoe2 mice were significantly elevated as compared with either mApoe Ϫ/Ϫ /htgApoe3 or mApoe Ϫ/Ϫ /htgApoe3L mice (Fig. 1A).…”
Section: Downloaded Fromsupporting
confidence: 86%
“…Transgenic mice expressing apoE2 and apoE3-Leiden in the absence of endogenous mouse apoE ( mApoe Ϫ / Ϫ /htgApoe2 and mApoe Ϫ / Ϫ /htgApoe3L ), which were previously described (30), were kindly provided by Dr. Havekes and Ko Willems van Dijk. LDLR-deficient mice ( mldlr Ϫ / Ϫ ) and double knockout mice homozygous for the absence of LDLR and apoE ( mApoe Ϫ / Ϫ /mldlr Ϫ / Ϫ ) were purchased from the Jackson Laboratory (Bar Harbor, ME).…”
Section: Animalsmentioning
confidence: 99%
“…This showed that LpL enhances this process and that ApoE is not an absolute requirement for binding, but results in isoform-dependent increased binding (72). Crossing APOE2TG and APOE3L mice on an apoe y/y ldlr y/y background showed that clearance of ApoE2-and ApoE3L-containing lipoproteins in the absence of the LDLR, and thus via alternative pathways such as LRP, is inefficient (73). This shows the pivotal role of the LDLR for clearance of VLDL remnants.…”
Section: Common Apoe Alleles In Mouse Modelsmentioning
confidence: 97%
“…In contrast, limited interaction of apoE2 with the LDLR enhances VLDL clearance and reduces remnant production in apoE2 livers. 21,40 Consequently, the overall degrees of reduction in LDL-cholesterol resulting from the increase in LDLR expression in humans is likely to be apoE-isoform-dependent; with more pronounced reduction in individuals with apoE2 but lesser reduction with apoE4.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Both adenovirus-mediated or global overexpression of the human LDLR in mice with apoE2 results in reduction of plasma cholesterol and TG and the absence of atherosclerosis. 17,21 Mice with human apoE3 and the Ldlr*h allele (Apoe 3/3 Ldlr h/ϩ ) have significantly decreased HDL-cholesterol but only a small increase in remnants and do not develop atherosclerosis. 18 In contrast, on a high-fat Western type diet, mice with apoE4 overexpressing the LDLR (Apoe 4/4 Ldlr h/ϩ ) have increased plasma very low density lipoproteins (VLDL)/ chylomicron remnants, decreased HDL-cholesterol levels, and develop atherosclerosis.…”
mentioning
confidence: 99%